2014
DOI: 10.17221/7653-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of diet amended by risk elements contaminated soils on risk element penetration and physiological parameters of rats

Abstract: ABSTRACT:The long-term accumulation of risk elements (As, Cd, Pb) originated from differently contaminated soils in rat organism was investigated during a model two-generation experiment. The effect of soil contamination level, gender, and length of exposure as well as the interactions between risk elements and selected essential macro-and microelements were studied. Rat diet contained 10% of individual soils (based on dry weight): (i) Fluvisol heavily polluted by As, Cd, Zn, and Pb, (ii) Luvisol contaminated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 49 publications
(59 reference statements)
2
6
0
Order By: Relevance
“…Additionally, competition with REs during uptake, absorption, and deposition may reduce the nal concentrations of essential elements in animal tissues(Whittaker et al 2011;Wang et al 2009). For instance, decreasing Zn levels in the organism exposed to elevated rates of Cd was published byMatovic et al (2012), and similar pattern was observed in our previous experiments with rat model(Vlčková et al 2014). The bioavailability of soil-borne elements depends on the characteristics of the soil (soil pH, element species in the soil, element binding on the soil particles, etc.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…Additionally, competition with REs during uptake, absorption, and deposition may reduce the nal concentrations of essential elements in animal tissues(Whittaker et al 2011;Wang et al 2009). For instance, decreasing Zn levels in the organism exposed to elevated rates of Cd was published byMatovic et al (2012), and similar pattern was observed in our previous experiments with rat model(Vlčková et al 2014). The bioavailability of soil-borne elements depends on the characteristics of the soil (soil pH, element species in the soil, element binding on the soil particles, etc.…”
supporting
confidence: 90%
“…Individals in control group recieved 139 ± 26 grams of fresh clover-grass biomass for the same period. The 10% w/w rate of soil was chosen according to our previous experiments with laboratory rat model (Vlčková et al 2014, Száková et al 2012). The element contents in the individual components of the diets are summarized in Table 1.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the RE uptake and especially the uptake of soil-borne elements cannot be unambiguously estimated from the results of the monitoring provided in the contaminated areas. Therefore, the effect of a diet amended with soil contaminated with As, Cd, and Pb on the element uptake and physiological and hematological parameters was previously investigated in laboratory conditions using a rat model (Mascolo et al 2004 ; Vlčková et al 2014 ; Száková et al 2012 ). However, the physiological and metabolic differences between laboratory strains of rodents ( Rattus and Mus ) and common wild species such as Microtus , Apodemus , and Myodes pose the pitfall of this methodological approach.…”
Section: Introductionmentioning
confidence: 99%